Bile acids affect intestinal barrier function through FXR and TGR5 - Song, Guangyao; Xie, Yuxiao; Yi, Lanlan; Cheng, Wenjie; Jia, Huijin; Shi, Wenzhe; Liu, Qiwei; Fang, Ligui; Xue, Shiqi; Liu, Dan; Zhu, Junhong; Zhao, Sumei (Frontiers in Medicine, 2025)
Bile acids play a dual role by aiding lipid absorption and acting as signaling molecules by interacting with various receptors. Bile acids are perpetually recycled via enterohepatic circulation and are biotransformation by gut microbiota, making bile acid metabolism a critical regulator of intestinal homeostasis. The intestinal epithelium prominently expresses two key bile acid receptors - the farnesoid X receptor (FXR) and G protein-coupled bile acid receptor 1 (TGR5) - which play indispensable roles in maintaining bile acid homeostasis and intestinal barrier function. Due to the abundant expression of bile acid receptors and the importance of the intestine in preventing pathogen invasion, researchers are increasingly focused on the function of bile acids in this system. This article focuses on the effect of bile acids and their receptors, FXR and the TGR5, in modulating intestinal barrier function.